1970
DOI: 10.1037/h0029813
|View full text |Cite
|
Sign up to set email alerts
|

Differential reinforcement of low rates: A selective critique.

Abstract: The literature relevant to the differential reinforcement of low rates of responding (DRL) is reviewed with respect to measurement of the behavior, bursts of responding, sequential dependencies, extinction and reconditioning, comparative aspects, punishment, reinforcement of two interresponse times, amount of deprivation and reinforcement, behavioral contrast, stimulus generalization, and response generalization. This review suggests that (a) bursts of responding could be due to a lack of stimulus feedback, (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
109
1
3

Year Published

1973
1973
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(117 citation statements)
references
References 72 publications
4
109
1
3
Order By: Relevance
“…et al (1974) work and others is that the Lowe et al subjects were presented with all levels of the inde· pendent variable in each session. Given that magnitude of reinforcement effects tend to be sensitive to the frequency of presentation of the different conditions (Kramer & Rilling, 1970), it seems reasonable to suggest that the Lowe et al results may be specific to the experimental design used in their study. Thus, the present study inquires as to whether the "unconditioned inhibitory effect" of reinforcement noted by Lowe and his co-workers would be found when performance was examined after prolonged exposure to each treatment condition.…”
Section: Ball State University Muncie Indiana 47306mentioning
confidence: 79%
“…et al (1974) work and others is that the Lowe et al subjects were presented with all levels of the inde· pendent variable in each session. Given that magnitude of reinforcement effects tend to be sensitive to the frequency of presentation of the different conditions (Kramer & Rilling, 1970), it seems reasonable to suggest that the Lowe et al results may be specific to the experimental design used in their study. Thus, the present study inquires as to whether the "unconditioned inhibitory effect" of reinforcement noted by Lowe and his co-workers would be found when performance was examined after prolonged exposure to each treatment condition.…”
Section: Ball State University Muncie Indiana 47306mentioning
confidence: 79%
“…EXPERIMENT 1 Experiment 1 explored the effects of signaled reward in a DRL schedule of reinforcement (see, e.g., Kramer & Rilling, 1970). We should note that both the overshadowing and efficiency hypotheses predict a lower rate of responding for the correlated subjects relative to the random animals.…”
mentioning
confidence: 99%
“…Many studies have been reported on this operant schedule with relatively short time values (20 seconds or less). It is known that by repeating the training under DRL, response rate decreases, median interresponse time (IRT) increases, and an IRT distribution pattern with a peak at around the schedule value gradually becomes prominent (Kramer & Rilling, 1970). This patterning is known as the temporal response pattern, which illustrates a timing process of animals (Sidman, 1959 hour were averaged over session 21 to 30 for each rat and plotted on log-log axes as a function of DRL values in Fig.…”
mentioning
confidence: 99%